An optimized method for directed differentiation of hypothalamic neural stem cells in a 3D culture system - Jiao Luo; Qiaoyan Tang; Tanjing Lin; Jiabang Liu; Zhiheng Wu; Xintao Zhang; Xiaohua Zhang; Junhai Jiang; Yulong Wang (Scientific Reports)
Abstract Hypothalamic neurogenesis is a complex process that plays a crucial role in neuroendocrine homeostasis, making in vivo studies of the hypothalamus particularly challenging. In this study, we present an optimized protocol for isolating and culturing hypothalamic neural stem cells (htNSCs) from neonatal (P1) mice, followed by their directed differentiation in a three-dimensional (3D) Matrigel environment. We successfully established a primary culture system that supports the stability, growth, and distinct characteristics of htNSCs. Notably, we demonstrate that htNSCs can differentiate into GnRH-like neurons within the Matrigel-based 3D culture system. These differentiated neurons exhibit typical neuronal morphology and functional characteristics. Our findings highlight the potential of neonatal htNSCs as an invaluable model for studying hypothalamic function and neurogenesis. Furthermore, this method provides a novel platform for basic research and may serve as important implications for further studying the pathological mechanism of neuroendocrine disorders in hypothalamus.